Christology of Alexander of Hales - Watson, Duncan S. (The University of Edinburgh, 1966)
This thesis is a venture of a person in the reformed tradition into thirteenth century scholastic theology, in particular, into the Christology of Alexander of Hales (died 1245). It is based especially on the Glossa on the Sentences of Peter Lombard. The quaestiones disputed before Alexander was a Franciscan are also taken into consideration. The Summa traditionally attributed to Alexander has not been used because it is a compilation of various authors. The main question of the thesis has been: what place does Alexander give the humanity of Christ? At only one place has Alexander's answer to this question been found to be satisfactory and that is where he has followed in the steps of Ansa Lai. Only when he treats of the doctrine of satisfaction for the temporal punishment of original sin does he give the humanity a necessary place, or, to put that another way, does he go beyond what is, in effect, Adoptlonlst Christology. His doctrine of Christ, by and large, leaves out of Christ's necessary work, eternal satisfaction for original sin, satisfaction for actual sins, forgiveness of guilt, and the sanctification of man. There are four aspects of hie thinking involved in this limited Christology. Whether they are presuppositions, causes or effects, is a matter for the history of theology. i) His presupposition of God as "One" in the neo-Platonic tradition. This prevents Alexander's conceiving of God's full involvement in creation. In his thinking on the uniting and on the hypostatic union he keeps God and man "at arm's length", first by distinguishing too much between Divine nature and Person, and then in the hypostatic union by distinguishing between hypostasis and person. The "One" is also seen as a presupposition in the discussion of Christ's suffering and relation to sin, and in Alexander's doctrine of predestination and "Poainus" where time and eternity are not discussed in view of the incarnation. ii) As a corollary man has a capacity for God. in Alexander's understanding of Christ this is seen as something akin to Apollinarianism, and elsewhere It Is seen In his view of Mary and the saints, of grace, freewill, and merit, and in the doctrine of the sacraments, particularly that of Penance. ill) His doctrine of grace, in particular regard to forgiveness and sanctifioation grace (or the Holy Spirit) takes the place of Jesus Christ. Grace Is viewed substantially and becomes "mediator" by means of the doctrine of uncreated and created grace. Christ Is, at best, a channel of this grace. iv) The doctrine of the priesthood and the sacraments. Here a mediatorial role is also assumed. It appears that priest and sacrament are man to God and God to man. Christ's power is forwarded to the Church which appears to replace the Holy spirit. The relationship of grace and the Holy Spirit is not definite. These viewpoints contribute to a limited Christology and prevent an incarnation centred doctrine of Christ.
The christology of Alexander of Hales
Keywords: Alexander, of Hales, approximately 1185-1245; Jesus Christ; Christology